2‐(Trimethylsilyl)‐λ3‐Phosphinine: Synthesis, Coordination Chemistry, and Reactivity. Issue 4 (11th December 2017) - Habicht, Marija H.; Wossidlo, Friedrich; Bens, Tobias; Pidko, Evgeny A.; Müller, Christian
Abstract: The [4+2] cycloaddition reaction between 2‐pyrone and Me3 Si−C≡P gives the corresponding 2‐(trimethylsilyl)‐λ 3 ‐phosphinine in good yields as a rather air and moisture stable, colorless oil. Insight into the regioselectivity of the pericyclic reaction was obtained with the help of deuterium‐labeling experiments. The silyl‐phosphinine acts as a ligand for the preparation of a Cu(I) and the first crystallographically characterized phosphinine‐Ag(I) complex. The title compound was further used as a starting material for an alternative preparation of the parent phosphinine C5 H5 P by means of protodesilylation with HCl. C5 H5 P reacts with CuBr⋅S(CH3 )2 to give an infinite Cu(I)Br coordination polymer. DFT calculations shed light on the influence of the ‐Si(CH3 )3 group on the electronic properties of the aromatic phosphorus heterocycle. Abstract : Phospha‐benzene analogues : 2‐(Trimethylsilyl)‐λ 3 ‐phosphinine can easily be prepared by a [4+2] cycloaddition between 2‐pyrone and (CH3 )3 Si−C≡P. Protodesilylation yields the parent phosphine C5 H5 P. The coordination chemistry was investigated, and DFT calculations give insight into the electronic properties of the phosphorus heterocycles.